Different levels of hydration following a training session on swimming performance - Toubekis, A.; Christoforou, N.; Laparidis, K.; Tahtalis, T.; Tokmakidis, S. (Biomechanics and Medicine in Swimming X, 2006)
This study examined the effects of two different levels of hydration after a training Session on subsequent performance. Eight swimmers performed a morning swimming training session, and 8 hours later a testing Session of 4x200m at an intensity of 95% of the critical velocity (4x200submax) and 200m maximum effort (200max). In two separate trials, swimmers consumed a fluid volume of either 150% (F150) or 50% (F50) of the morning post-training body mass (BM) loss. BM was reduced by 0.9±0.2% and 0.8±0.3% after the morning Session in F150 and F50 trials respectively (p>0.05). Eight hours later, BM had recovered in the F150 but not in the F50 trial (p<0.05). Heart rate showed a tendency to increase at the end of the 4x200submax (p=0.08). The 200max time was not different between trials (p>0.05). As a result dehydration of 1% might not be a critical factor in impairing performance during a 200max.